William of Ware’s Arguments in Defense of Mary’s Immaculate Conception - Salvador-González, José María (Verbum Vitae, 2025)
The current article aims to shed light on the reasoning used by the 13th century English Franciscan master William of Ware to defend the belief in the immaculate conception of the Virgin Mary. To do so, this English theologian begins by dismantling the alleged reasons of those who opposed such belief. He then examines the numerous proofs that, in his opinion, confirm the truth of the thesis under study. As a methodological strategy, the author of this article sets out step by step and in detail the interrelated arguments of William of Ware to rationally support his defense of the immaculate conception thesis. The results of this research highlight the courageous and innovative pro-immaculate stance of William of Ware in the face of the then dominant current of deniers of the belief in the immaculate conception of Mary.